Keeping an Open Mind: Cognitive Bias in the Evaluation of an Infant with Posterior-Lateral Rib Fractures. (26th October 2017) - Johnson, Katie; Derauf, Donald Chris; Stetson, Raymond; Galardy, Paul; Homme, Jason
Abstract : A four-month-old former premature male is incidentally found to have posterior-lateral rib fractures during evaluation of a febrile illness. This finding led to the initiation of a workup for nonaccidental trauma. A thorough history and physical exam ultimately led to the diagnosis, which was not related to abuse. This case highlights a rare sequela of patent ductus arteriosus repair, cautions medical teams to remain aware of how cognitive bias can affect diagnostic decision-making, and emphasizes the importance of a thorough history, physical exam, and medical record review in cases of suspected nonaccidental trauma.